JURISDICTIONAL ACTIVITY OF INTERNAL AFFAIRS BODIES (Journal of actual problems of jurisprudence, 2019)
This article discusses the legal basis of jurisdictional activities O.V.D on the application of administrative law, as well as theconcept and features of the administrative - jurisdictional activities of internal affairs.